1989
DOI: 10.1007/bf02624010
|View full text |Cite
|
Sign up to set email alerts
|

A simple, disposable, and improved organ culture system for maintaining three-dimensional development of mouse embryonic molars

Abstract: Mandibular first molars from 17-d-old mouse embryos were cultured in vitro for 2 to 4 d by a simple, disposable, improved floatation method. This method consisted of using a 24-well multidish and a plastic culture chamber with a membrane filter. The improved floatation method, as well as our previous method, was capable of the three-dimensional development of tooth germs. Cytodifferentiation of odontoblasts and ameloblasts and formation of extracellular matrices were accelerated by the present culture system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In vitro methods of culturing tooth germ have been used widely to explore intracellular and extracellular mechanisms involved in odontogenesis. For more accurate results, it is necessary to employ an organ culture system to simulate conditions in vivo . This study found that the RCCS was able to supply efficient high nutrient transfer, low shear force, and microgravity suitable for the development of tooth germs with appropriate spatial morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro methods of culturing tooth germ have been used widely to explore intracellular and extracellular mechanisms involved in odontogenesis. For more accurate results, it is necessary to employ an organ culture system to simulate conditions in vivo . This study found that the RCCS was able to supply efficient high nutrient transfer, low shear force, and microgravity suitable for the development of tooth germs with appropriate spatial morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the shape and spatial arrangement of the resultant tooth germs, however, were observed. Application of this method was also hindered by a complex manufacturing process, with which it was difficult to obtain a uniform agar chamber. In each of the aforementioned studies, tooth germ ingrowth stopped after several days of culture, which indicates that tooth germ development is limited in a relatively static culture environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in vivo tissue based bone inductive studies remain to date the best models to study the effect of biomaterial behavior in vivo. As such, a tissue-based bioreactor platform [23,29,30] could be superior to that of a stem cell-based system as tissues possesses various biochemical building blocks and adult stem cell niches together with preestablished cell growth promoting environments that theoretically could provide a superior culturing milieu. However, the use of bone directly as a biomaterial growth environment in vitro is highly problematic, as culture medium cannot adequately diffuse across a hard tissue barrier [30].…”
Section: Introductionmentioning
confidence: 99%
“…As such, a tissue-based bioreactor platform [23,29,30] could be superior to that of a stem cell-based system as tissues possesses various biochemical building blocks and adult stem cell niches together with preestablished cell growth promoting environments that theoretically could provide a superior culturing milieu. However, the use of bone directly as a biomaterial growth environment in vitro is highly problematic, as culture medium cannot adequately diffuse across a hard tissue barrier [30]. Therefore, the present pilot study investigated the feasibility of two in vitro skeletal muscle-based biomaterial-culturing systems as this tissue, being considered among the promising candidate grafts for bone tissue engineering, allows for better nutrient flow [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in vivo tissue based bone inductive studies remain to date the best models to study the effect of biomaterial behavior in vivo. As such, a tissue-based bioreactor platform [23,29,30] could be superior to that of a stem cell based system as tissues poses various biochemical building blocks and adult stem cell niches together with pre-established cell growth promoting environments that theoretically could provide a superior culturing milieu. However, the use of bone directly as a biomaterial growth environment in vitro is highly problematic, as culture medium cannot adequately diffuse across a hard tissue barrier [30].…”
Section: Introductionmentioning
confidence: 99%